Review on Energy Bar by Utilizing Dates and Cantaloupe Seeds - Rushikesh D. Kulkarni; Deepak T. Bornare; Swapnil G. Jaiswal (Archives of Current Research International, 2025)
Energy bars are experiencing an increase in popularity attributable to their convenience and associated health advantages, with a particular emphasis on natural and functional ingredients. This study aimed to develops of energy bar by using dates (Phoenix dactylifera) and cantaloupe seeds (Cucumis melon L.) As primary constituents. Dates, known for their natural sweetness, high fiber content, and rich nutrient profile, give a quick and sustained energy release, making them an ideal base for energy bars. They’re abundant in essential minerals like potassium and magnesium, which support muscle function and electrolyte balance, and are also packed with antioxidants that help combat oxidative stress. Cantaloupe seeds, frequently overlooked in nutrition products, are rich in protein, healthy fats, and salutary fiber, farther enhancing the bar’s nutritive value. This combination not only offers a natural and healthy source of energy but also supports digestive health, muscle recovery, and overall well- being. The bar is free from refined sugars and artificial complements, making it a wholesome, factory- grounded snack ideal for athletes and active individualities. This product provides a sustainable, functional volition to traditional energy bars, feeding to the growing demand for clean, nutrient- thick snacks in the health and heartiness request.